Clinical and epidemiological profile of patients with severe H1N1/09 pandemic influenza in Australia and New Zealand: an observational cohort study - Allen C Cheng; Christine Jenkins; Louis Irving; Richard Wood-Baker; Tom Kotsimbos; Robert J Hancox; Anna Reynolds; Simon G A Brown; Graham Simpson; Simon D Bowler; Mark Holmes; Philip Thompson; et al. (BMJ Open)
Background Pandemic influenza H1N1/09 emerged in April 2009 and spread widely in Australia and New Zealand. Although an unprecedented number of cases required intensive care, comparative community-based studies with seasonal influenza strains have not shown any significant differences in clinical symptoms or severity.Methods The authors performed active surveillance on confirmed influenza-related admissions and compared the clinical profile of patients with pandemic H1N1/09 influenza and patients with seasonal influenza at eight hospitals in Australia and one hospital in New Zealand.Results During the 1 July and 30 November 2009, 560 patients with confirmed influenza were admitted, of which 478 had H1N1/09, and 82 had other seasonal strains. Patients with H1N1/09 influenza were younger, were more likely to have fever and were more likely to be pregnant but less likely to have chronic obstructive pulmonary disease and ischaemic heart disease than patients with seasonal strains. Other clinical features and comorbidities were reported in similar proportions. Admission to intensive care was required in 22% of patients with H1N1/09 influenza and 12% in patients with other strains. Hospital mortality was 5% in patients with H1N1 influenza.Conclusions The clinical features of H1N1/09 influenza and seasonal strains were similar in hospitalised patients. A higher proportion of patients had comorbidities than had been reported in community-based studies. Although the overall mortality was similar, the authors found evidence that H1N1/09 caused severe disease in a higher proportion of hospitalised patients.